Report on the First International Symposium Science in Judo (ISSJ) - Mateo-Cubo, Félix; Montero-Carretero, Carlos (Revista de Artes Marciales Asiáticas, 2017)
This report resumes the First International Symposium Science in Judo (ISSJ), organized by the Department of Health Psychology, Miguel Hernández University, Elche (Spain), and held from October 12 to 14h, 2017. During this symposium some of the most relevant research projects related to judo as a sport were presented. There were a wide variety of topics, including biomechanics of technique, health, psychology, nutrition, sport training, education and future prospects. Five plenary sessions, six mini-sessions, one panel discussion and two workshops on tatami were developed. The symposium was an event where important national and international researchers participated. It was intended for groups related to judo, such as Sports Sciences students, judo coaches and high level judo athletes. More than 70 people participated in the symposium whose main aim was to provide scientific evidence on judo to judo professionals.